STATUS PENGUASAAN TANAH TIMBUL (AANSLIBBING) DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - RUDIANSYAH PULUNGAN (PREMISE LAW JURNAL, 2013)
ABSTRACT As a new plain, a naturally emerging land is a plain with the potential and economic values to be utilized. Up to now, the explicit regulation on the control over the naturally emerging land has not yet found in the Indonesian Agrarian Law. The purpose of this study was to examine more about the control over the naturally emerging land according to the customs of local communities, the status of the control over the naturally emerging land, and the steps taken to acquire the right to land related to the control over the naturally emerging land in Rengat Subdistrict, Indragiri Hulu District.This empirical (sociological) juridical study looked at the aspect of legal application in the society or the communities’ behavior generated due to the interaction conducted based on the existing norm system. The data obtained were qualitatively analyzed to provide a clear description on the answer to the problems studied. To draw a conclusion, the result of this data analysis was process through deductive method. Keywords: Naturally Emerging Land, Land ControlABSTRACT As a new plain, a naturally emerging land is a plain with the potential and economic values to be utilized. Up to now, the explicit regulation on the control over the naturally emerging land has not yet found in the Indonesian Agrarian Law. The purpose of this study was to examine more about the control over the naturally emerging land according to the customs of local communities, the status of the control over the naturally emerging land, and the steps taken to acquire the right to land related to the control over the naturally emerging land in Rengat Subdistrict, Indragiri Hulu District.This empirical (sociological) juridical study looked at the aspect of legal application in the society or the communities’ behavior generated due to the interaction conducted based on the existing norm system. The data obtained were qualitatively analyzed to provide a clear description on the answer to the problems studied. To draw a conclusion, the result of this data analysis was process through deductive method. Keywords: Naturally Emerging Land, Land Control